2009
DOI: 10.1089/ars.2008.2412
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: Its Biologic Targets and Functional Activity

Abstract: The polyphenolic phytoalexin resveratrol (RSV) and its analogues have received tremendous attention over the past couple of decades because of a number of reports highlighting their benefits in vitro and in vivo in a variety of human disease models, including cardio- and neuroprotection, immune regulation, and cancer chemoprevention. These studies have underscored the high degree of diversity in terms of the signaling networks and cellular effector mechanisms that are affected by RSV. The activity of RSV has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
265
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(270 citation statements)
references
References 423 publications
5
265
0
Order By: Relevance
“…Resveratrol (3,5,4′-trihydroxy-trans-stilbene) is a stilbenoid, a type of natural polyphenol compound, and a phytoalexin produced naturally by several plants especially the roots of the Japanese Knotweed when challenged from bacterial or fungal attack. Diverse effects of resveratrol as cardioprotective, anticarcinogenic, immunomodulatory, antioxidant, and antiapoptotic agent have been reported previously [12,17,33]. One of the most robust and reproducible effects of resveratrol is to increase the mitochondrial mass [3,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol (3,5,4′-trihydroxy-trans-stilbene) is a stilbenoid, a type of natural polyphenol compound, and a phytoalexin produced naturally by several plants especially the roots of the Japanese Knotweed when challenged from bacterial or fungal attack. Diverse effects of resveratrol as cardioprotective, anticarcinogenic, immunomodulatory, antioxidant, and antiapoptotic agent have been reported previously [12,17,33]. One of the most robust and reproducible effects of resveratrol is to increase the mitochondrial mass [3,22].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol is produced by the interaction of plants with a microorganism present in the roots of Polygonum cuspidatum , Vitis vinifera , red wines, and mulberries and protects these plants against fungal and bacterial infections [23]. Resveratrol exhibits wide variety of pharmacological properties like anti-inflammatory, chemopreventive, antioxidant, antiproliferative, proapoptotic, cardioprotective, and anticancer effects [12,33]. It also controls the expression of different genes related to DNA synthesis, cell cycle, proliferation, stress response and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the antioxidant, anti-inflammatory and anti-tumoral effects of resveratrol (Delmas et al, 2006;Pervaiz and Holme, 2009) have been widely described, the cellular toxicity was not yet completely evaluated, especially regarding mitochondrial bioenergetics.…”
Section: Discussionmentioning
confidence: 99%
“…Following previous works showing protective effects of resveratrol on brain and liver (Morin et al, 2003;Park et al, 2010;Pervaiz and Holme, 2009), the present work investigates its toxicity on isolated brain and liver mitochondria at concentrations that act to decrease oxidative stress. The use of brain and liver mitochondria was due to the fact that resveratrol is able to cross the BBB (Wang et al, 2002) and it is highly metabolized in the liver (Walle, 2011), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, it was shown to exhibit calorie restriction-like effects on energy metabolism and metabolic profile in obese humans. 20,21,[31][32][33] It is a safe and natural supplement. 34 Resveratrol also protects against the teratogenic effects of dioxin in pregnancy.…”
Section: Discussionmentioning
confidence: 99%